The Effectiveness of Talent Management Practices on Generation-Y Employees: A Case Study of Telekom Malaysia Berhad - Khan, Arsalan Maroof (2013)
The telecommunication industry has now become one of the leading information brokers of the world. The advent of new cutting-edge technologies and state-of-the-art services thereof have dramatically revolutionized this era. To cater and accommodate the ever rising demands of information, telecommunication giants have intensified investments in their infrastructure many times over. Functionality and operations of such gigantic corporations and massive enterprises necessitate colossal human capital. With employees in thousands; Telekom Malaysia Berhad needs to employ and utilize very strong and efficient talent management programs. Talent management is the name associated to the Human Resources Department activities of ‘Hiring’, ‘Training and Development’, ‘Evaluating’ and ‘Rewarding’ people who form the backbone of company’s operations. Each activity and associated disciplines play an important part in the overall talent management strategy. All related, coherent and rational strategies must be effectively aligned to form a dynamic apex of the progressive 3D road map and general direction of the company as it endeavors to achieve and implement its mission and vision. The company leaders and architects of the overall talent management structures and programs are mostly baby boomers and Gen X employees. However the programs they design are being engaged to mostly Gen Y employees. Literature review suggests that rapid advancements and the new technological epoch has created a visible generation gap between expectations, requirements and work habits of Gen Y and Gen X or baby boomers. The objective of this research is to explore the talent management practices of Telekom Malaysia Berhad as designed by Gen X managers and executives, and how they are perceived by Gen Y employees. The research revealed that Telekom incorporates and rightly boasts well formulated and intelligently designed hiring and training programs. However, participants of the in depth survey reflected that performance reviews and rewards systems are still weak as compared to the market. However there is much to suggest that by upgrading performance review systems and reward programs Telekom Malaysia Berhad can become one of the foremost and leading GLCs in Southeast Asia.